The Poet and Owning Previous Text, Ibn al-Roumi as a Model (Journal of Human Sciences, 2020)
Text-making depends on the existence of cultural structures, whether prose or poetic before it. that merges with the poet’s reality and appears in his new text, consciously or unconsciously. The essence, which confirms his ability to regenerate, as the poet freezes the text, but does not destroy its structures and predicates and tries to reformulate it and produce it according to the requirements of the historical moment. The text appears in a more creative form than the previous text, despite its increase in meaning. Ibn al-Rumi's poetry is a model for the creative poet's ability to possess the previous text and build upon it in producing his present text according to the requirements of his era.